IDEALS AND TRANSGRESSIONS IN THE MIDST OF PRECARIOUSNESS: THE “CASA DE RECOGIDAS” FROM SANTIAGO, CHILE, 17TH-18TH CENTURIES”. - Onetto Pavez, Mauricio (Revista de Historia Social y de las Mentalidades, 2025)
The present article focuses on the institutionalization process of the “Casa de Recogidas” of Santiago, Chile, as well as on the way it functioned and controlled within the 18 th century’s Santiaguinian society. The study aims to analyze how an institution –with universal structures and principles– had to adequate itself to a precarious reality in socio-cultural and material terms, and how this situation determined its development.